Analysis of the Influence of Talent and Competency Management on Performance Moderated by Organizational Commitments in The Environment of the Church of the Assembly of Allah (GSJA) In Jayapura - Thobby Wakarmamu (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to obtain empirical evidence and develop a theory (prediction orientation) The Effect of Talent Management and Competence on Performance Moderated by Organizational Commitment in the Assemblies of God Church (GSJA) in Jayapura. Seeing the problems and research objectives to be achieved, this research uses an explanative research approach with a survey approach. The questionnaire was prepared based on the variables of talent management, competence, performance and organizational commitment. The research data were taken from 30 respondents. which is the sample of this study. Data collection is done by random sampling technique. In this study, data analysis used the Partial Least Square (PLS) approach using Smart PLS software. PLS is a component-based or (variance) structural equation model (SEM). The results of his research show that: talent managementaffect performanceproved fromthe t statistic is 17,498 with a P value of 0.000 < from 0.05, this shows that the higher the talent management, the higher the performance. Competence affects performanceproved fromthe value of t statistic is 3.123 with P value of 0.002 < from 0.05, this indicates that the higher the competence, the higher the performance. Talent management affects organizational commitmentproventhe t statistic is 13,813 with a P value of 0.038 < from 0.05, this indicates that the higher the talent management, the higher the organizational commitment. Competenceaffect organizational commitmentprovent value 3.128 with P value 0.002 < from 0.05, this means that the highercompetence, the higher the organizational commitment. Performanceaffect organizational commitmentproved fromthe value of t statistic is 32.899 with a P value of 0.000 < from 0.05, this indicates that the higherperformance, the higher the organizational commitment.There is an indirect effecttalent management on performance through organizational commitmentP-values 0.000 > 0.05. Indirect effect resultscompetenceon performance through organizational commitmentP-values 0.002 < 0.05 this means significant.